Severity and risk of COVID‐19 in cancer patients: An evidence‐based learning. Issue 5 (3rd July 2020) - Sharma, Akanksha; Malviya, Rishabha; Kumar, Vinod; Gupta, Ramji; Awasthi, Rajendra
Abstract: The immune system of cancer patient gets compromised because of cancer therapy, surgery, and malignancy and thus the probability of infection are increased than the general patients. Immunosuppression can expose cancer patients to serious complications which can lead to delay in diagnosis and unnecessary hospitalizations that may adversely affect the prognosis of the disease. Patients who received chemotherapy or surgery within the 30 days before novel coronavirus disease pandemic have more risk of infection than the patients who had not undergone chemotherapy or surgery.